Spray drift characteristics of pulse-width modulation sprays in wind tunnel - Li, Longlong; Chen, Liping; Zhang, Ruirui; Tang, Qing; Yi, Tongchuan; Liu, Boqin; Deng, Wei (International Journal of Agricultural and Biological Engineering, 2022)
Pulse-width modulation (PWM) sprays can improve flow accuracy by adjusting duty cycle and frequency signal which accurately controls the relative proportion of opening time of solenoid valve. The objective of this research was to determine the impacts of PWM duty cycle and frequency on spray drift characteristic. Spray tests were conducted in a wind tunnel with a PWM variable-rate spraying system. The airborne drift and sediment drift were determined with tracer method, and the drift potential reduction (DPR) compared with reference condition of 100% duty cycle at vertical profile and horizontal planes were calculated, respectively. The results show that, at a given frequency, droplet size decreases with the increase of duty cycle, the main reason is that the liquid does not reach full pattern development at lower duty cycle. Duty cycle has a greater impact than the frequency on spray drift, the influence weights of duty cycle on airborne drift and sediment drift were 88.32% and 77.89%, respectively. At a lower PWM frequency, in addition to the droplet size, the spray drift may be affected by the pulsed spray pattern. From the perspective of reducing spray drift, it is recommended that the PWM duty cycle should be set in the range of 20%-70% to reduce the potential drift in PWM sprays. This research provides a pesticide drift reduction scheme for variable spraying technology, which can serve as a theoretical basis for PWM parameter selection.Keywords: nozzle, spray drift, pulse-width modulation, drift potential reduction, droplets spectralDOI: 10.25165/j.ijabe.20221504.7440Citation: Li L L, Chen L P, Zhang R R, Tang Q, Yi T C, Liu B Q, et al. Spray drift characteristics of pulse-width modulation sprays in wind tunnel. Int J Agric & Biol Eng, 2022; 15(4): 7–15.